2018
DOI: 10.3390/sports6020045
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Three Measures of Reaction Time Based on Hand Laterality in Individual Sports

Abstract: (1) Aim: The study aimed at assessing simple-reaction, recognition and cognitive-reaction times to visual stimuli among student athletes: boxing, gymnastics, taekwondo, judo, karate and wrestling, using computer games tests. (2) Methods: Our study involved 332 students and athletes. We applied three types of computer tests to measure the dominant and non-dominant hands: the simple motor reaction time through the Human Benchmark test, the recognition time by the Hit-the-dots and the cognitive reaction time by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 20 publications
3
45
0
6
Order By: Relevance
“…Reaction time is a term described as the time between the impulse and movement (Badau et al, 2018) and in athletics, it is defined as the signal of a start coordinator and the pressure that athletes apply on the starting block. Theoretically, if an athlete starts to move any time after the signal, the start is deemed valid.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction time is a term described as the time between the impulse and movement (Badau et al, 2018) and in athletics, it is defined as the signal of a start coordinator and the pressure that athletes apply on the starting block. Theoretically, if an athlete starts to move any time after the signal, the start is deemed valid.…”
Section: Introductionmentioning
confidence: 99%
“…We have found the median BasalRT to be 380.50 ms. The average BasalRT varies between 230-295 ms in the literature depending on the participant performing regular exercise, profession, gender and age (18)(19)(20)(21)(22). In this research, we have found that gender and age were insignificant in the BasalRT.…”
Section: Discussionmentioning
confidence: 47%
“…However, the current study found similar results with one exception that is basketball players' target throws did not change as well as the non-target non-ironic error rates across anxiety conditions. More specifically, for aiming type of tasks such as basketball free throw, dart throwing, pistol shooting, a particular fixation termed the quiet eye (Vickers, 1996), defined as the final fixation to a target before the initiation of the motor response (Badau, Baydil, & Badau, 2018), can become less efficient while performer has to perform under pressure. Therefore, taking a deep breath and not to hurry could allow performers an extended duration of programming while minimizing distractive or unwanted thoughts.…”
Section: Discussmentioning
confidence: 99%